The thermal model on the verge of the ultimate test: particle production in Pb-Pb collisions at the LHC - Andronic, Anton; Braun-Munzinger, P.; Redlich, K.; Stachel, Johanna (Journal of physics. G, Nuclear and particle physics, 2011)
We investigate the production of hadrons in nuclear collisions within the framework of the thermal (or statistical hadronization) model. We discuss the light-quark hadrons as well as charmonium and provide predictions for the LHC energy. Even as its exact magnitude is dependent on the charm production cross section, not yet measured in Pb-Pb collisions, we can confidently predict that at the LHC the nuclear modification factor of charmonium as a function of centrality is larger than that observed at RHIC and compare the experimental results to these predictions.